Memperkuat Fondasi Negara Hukum di Indonesia - Giawa, Irfan Niat Novriyanti; Nofya Cantika Nurfitriani; Stefani Lidia Fanil (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
The unitary state of the Republic of Indonesia is a legal state that upholds the supremacy of law and justice for all its citizens. However, in practice, Indonesian law enforcement officials still face various challenges and obstacles that threaten the integrity of the country. the realization of justice and equality throughout the country. The aim of this journal is to analyze the foundation of Indonesian legal supremacy in Indonesia and identify steps that can be taken to improve fair and objective law enforcement in Indonesia.